The mechanism of interaction between lotus rhizome polyphenol oxidase and ascorbic acid: Inhibitory activity, thermodynamics, and conformation analysis. Issue 5 (3rd February 2022) - Li, Caiyun; Li, Jie; Yan, Shoulei; Wang, Qingzhang
Abstract: In this study, the interaction between lotus rhizome polyphenol oxidase (PPO) and ascorbic acid (AA) was discussed from the aspects of inhibitory activity, thermodynamics, and conformation. Results showed that PPO was purified from lotus rhizome by DEAE‐52 anion exchange chromatography and Sephadex G‐100 gel filtration chromatography, with its optimum substrate being determined as pyrogallic acid. Spectrophotometric and polarographic assays demonstrated that AA exhibited strong inhibitory activity against PPO. Thermodynamics, fluorescence, and circular dichroism spectral analysis showed that hydrophobic interactions caused the formation of AA–PPO complex, leading to the remarkable fluorescence quenching and conformational change of PPO. Atomic force microscopic analysis revealed that binding to AA induced significant changes in the surface morphology and molecular aggregation of PPO molecules. In this study, the interaction mechanism between PPO and AA was proposed for the first time, which provided a theoretical basis for AA to inhibit lotus rhizome browning. Practical applications: Lotus rhizome, an aquatic vegetable, is prone to enzymatic browning in processing operations, which leads to a decrease in market value and economic loss. At present, ascorbic acid (AA) is widely used in industries as an excellent antioxidant because of its good antibrowning effect and relatively low cost. However, the interaction between the enzymatic browning‐related polyphenol oxidase (PPO) from lotus rhizome and ascorbic acid has not been clearly studied. Understanding the mechanism of inhibiting PPO will help to prevent vegetable browning, especially fresh‐cut products. The inhibitory effect of AA on PPO in lotus rhizome favors simultaneous use with other types of PPO inhibitors because of their likely synergistic effects. Abstract : Polyphenol oxidase (PPO) of lotus rhizome was purified, and its optimum substrate was pyrogallic acid. Ascorbic acid (AA) inhibited the activity of PPO in lotus rhizome, and there was a hydrophobic interaction between both.